Penerapan Metode Nature Learning untuk Meningkatkan Motivasi Belajar Siswa Kelas VII-D SMP Brawijaya Smart School pada Pembelajaran Menulis Puisi - Muhammad Zanika Esa Putra; Auliya Rahma Zain; Machrus Abadi (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2024)
This study aims to reveal (i) what factors cause students' learning motivation to be difficult to increase in learning to write poetry; (ii) what solutions are offered to increase students' learning motivation in learning to write poetry; and (iii) whether the nature learning method is effectively applied to increase students' learning motivation in learning to write poetry. This study was conducted in class VII-D of SMP Brawijaya Smart School, totaling 32 students, in the 2024/2025 academic year. The type of research used is experimental research with a mixed approach. The data analysis technique was carried out through two stages, namely on the results of interviews and observations, as well as on the results of measurements through questionnaires. The results showed that there are several factors that make student motivation difficult to increase in learning to write poetry. First, the lack of preparation from the teacher. Second, teachers tend to be monotonous when teaching in class. Based on these problems, the solution offered by the teacher is to use LKPD (Learner Activity Sheet). Next, teachers design interesting learning strategies. Teachers can use digital media in which there are games or quizzes. The application of the nature learning method in learning to write poetry for students of class VII-D of SMP Brawijaya Smart School is effective. This is shown through the data of the percentage of the effectiveness of this method at 64.3%. Then, students of class VII-D SMP Brawijaya Smart School feel motivated when learning outside the classroom with a percentage of 64.3%. Next, students felt happy with the implementation of the nature learning method, with a percentage of 57.1%. In addition, students of class VII-D SMP Brawijaya Smart School felt very helped and helped by the application of the nature learning method to develop their creative ideas. The percentage data shows that students feel very helped and helped by the application of the nature learning method, which is at 35.7%.